Pengetahuan Menginang berhubungan dengan Keluhan Rongga Mulut pada Lansia di Kabupaten Sampang Madura - Emdat Suprayitno; Mujib Hannan; Alfi Laila (Fakultas Kedokteran Gigi Universitas Jember, 2021)
Broadly speaking, periodontal tissue disease can be caused by two factors, namely local and systemic factors. These factors can be further aggravated by the presence of predisposition factors, such as host. The purpose of this study was to know relationship of betel knowledge with oral cavity complaints in the elderly in Taman village 2019. This study was cross sectional analytic research. The target in this study were elderly chewing betel in Taman Village, amounting to 32 elderly people. Methods of data collection knowledge of chewing betel used questionnaires and oral cavity complaints using observation. The analysis of this study used the is chi square test analysis. The analysis of is chi square test was significant which was 0,045 (p<0,05). Conclusion was there was relationship of chewing betel with oral cavity complaints in elderly in the jrengik village public health center.